Addressing health literacy gaps in adjuvant endocrine therapy adherence: Post hoc insights from a randomized remote monitoring trial - Ilana Graetz; Samuel Hernandez; Xin Hu; Rebecca A. Krukowski; Janeane N. Anderson; Teresa M. Waters; Edward Stepanski; Gregory A. Vidal; Lee S. Schwartzberg (Breast)
Adjuvant endocrine therapy (AET) improves survival in hormone receptor-positive breast cancer, yet adherence is often lower among individuals with limited health literacy. This post hoc analysis of the THRIVE trial examined whether health literacy modified the effectiveness of two remote monitoring interventions (App-only and App + Feedback) versus enhanced usual care (EUC) on 12-month AET adherence (≥80 % of prescribed doses via connected pillbox). Among participants with lower health literacy, adherence was higher with App + Feedback than EUC (80.0 % vs. 42.1 %, p = 0.03), with no significant differences among those with higher health literacy. Tailored digital interventions may support adherence among patients with limited health literacy. Trial: ClinicalTrial.gov identifier NCT03592771.